Pengaruh Faktor Psikologis dan Regulasi Terhadap Perilaku Konsumsi Energi Listrik Sektor Rumah Tangga Berdasarkan Usia - Maria Isfus Senjawati; Lisa Susanti; Hilma Raimona Zadry; Gustiarini Rika Putri (INVENTORY: Industrial Vocational E-Journal On Agroindustry, 2020)
The increase in household electrical energy causes shrinkage of energy so that efforts are needed to conserve energy, especially electrical energy. One attempt to reducing the scarcity of electrical energy is by changing behavior. Changes in the behavior of electricity consumption can be influenced by psychological factors (norms, awareness, etc.), demographic factors (age, gender, income, etc.), and other factors such as regulations or policies from the government to conserve energy. This study seeks to determine the effect of psychological and regulatory factors on the behavior of household electricity consumption based on age. The method used was to conduct a survey by distributing questionnaires, the respondents obtained were 808 respondents. The results of the questionnaire were processed using the Structural Equation Model Partial Least Square (SEM-PLS) using the Smart-PLS software. The results of this study indicate that psychological and regulatory factors can explain their effect on the behavior of electrical energy consumption for ages <30 years of 50.9%. For 30-50 years old it is 49.5% while those> 50 years old are 59.3% and the rest is explained by other factors / variables outside those that have been studied so that it can be concluded that psychological factors and regulatory factors have a significant and significant influence. positive behavior towards household electrical energy consumption at all ages. it is expected that the results of this study can become the basis for making stronger regulations or policies in the field of energy conservation.